1988
DOI: 10.1128/jb.170.12.5507-5511.1988
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction in chemotaxis to oxygen in Escherichia coli and Salmonella typhimurium

Abstract: Pathways previously proposed for sensory transduction in chemotaxis to oxygen (aerotaxis) involved either (i) cytochrome o, the electron transport system, and proton motive force or (ii) enzyme 11Iu'co" and the phosphoenolpyruvate:carbohydrate phosphotransferase system for active transport. This investigation distinguished between these possibilities. Aerotaxis was absent in a cyo cyd strain of Escherichia coli that lacked both cytochrome o and cytochrome d, which are the terminal oxidases for the branched ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…The 21% oxygen at the frequency of direction changes in response to chemoeffectors. meniscus neither attracted the motile cells as observed for aerDirection changes occur when the direction of swimming is obic species of bacteria [20], nor repelled the cells as observed reoriented during periodic tumbling (E. coli), reversal (Halofor facultative anaerobic and microaerophilic species [7,8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 21% oxygen at the frequency of direction changes in response to chemoeffectors. meniscus neither attracted the motile cells as observed for aerDirection changes occur when the direction of swimming is obic species of bacteria [20], nor repelled the cells as observed reoriented during periodic tumbling (E. coli), reversal (Halofor facultative anaerobic and microaerophilic species [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Institute of Biochemistry and Physiology of cells with oxygen using a tetraphenylphosphonium (TPP÷)-selective Plants and Microorganisms, Russian Academy of Sciences, Saratov, electrode, as previously described [7]. Cells were made permeable to 410015 Russian Federation.…”
Section: Membrane Potential Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of the behavioral responses of E. coli to oxygen (2,44), other terminal electron acceptors (5), redox molecules (electron carriers) (9), and rapidly metabolized carbon sources (electron donors) (10) demonstrated that a signal for each of these behaviors is generated in the electron transport system. Electron transport and proton motive force are tightly coupled, so it is not possible at this time to distinguish which is the signal for bacterial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments, we have isolated and purified the Aer protein and found a noncovalently bound cofactor that comigrates with FAD in the HPLC profiles (unpublished data). The midpoint redox potential of FAD͞FADH 2 is Ϫ220 mV; the redox potential of Aer-bound FAD is likely to be in the range that permits interaction with dehydrogenases (Ϫ300 mV range) and͞or with ubiquinone (ϩ113 mV) and menaquinone (Ϫ74 mV) (9,44,45). As a result, Aer may sense changes in the electron transport between dehydrogenases and quinones.…”
Section: Discussionmentioning
confidence: 99%